2022
DOI: 10.1038/s41387-022-00227-x
|View full text |Cite
|
Sign up to set email alerts
|

The association of maternal fat-soluble antioxidants in early pregnancy with gestational diabetes mellitus: a prospective cohort study

Abstract: Introduction Oxidative stress is linked to the development of gestational diabetes mellitus (GDM). Maternal antioxidant vitamins in early pregnancy may play a role in GDM occurrence. We aimed to investigate the associations of vitamins A and E in early pregnancy with the risk of GDM and to explore whether these antioxidant vitamins can be biomarkers for the early prediction of GDM. Methods We carried out a prospective cohort study conducted in Beij… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…All available previous studies conducted the analyses based on the hypothesis that the association between VE concentration and GDM was linear [ 17 ]. The aforementioned systematic review by Sharifipour et al concluded that the VE level was significantly lower in women with GDM compared to healthy pregnant women [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All available previous studies conducted the analyses based on the hypothesis that the association between VE concentration and GDM was linear [ 17 ]. The aforementioned systematic review by Sharifipour et al concluded that the VE level was significantly lower in women with GDM compared to healthy pregnant women [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E (VE), a well documented antioxidant, can neutralize ROS, eliminate oxygen free radicals, and protect tissue from damage [ 9 , 10 ]. However, although a robust number of studies on the role of VE in the cause and prevention of diabetic complications [ 8 , 11 , 12 , 13 , 14 , 15 ], there are very few studies on its association with risk of diabetes mellitus, especially GDM [ 16 , 17 ]. The systematic review by Sharifipour et al aimed to evaluate the association between VE and GDM, and this only included eleven relevant studies with a total of 596 participants published before December 2019, of which seven were the case-control studies, and the rest were cross-sectional [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While some level of oxidative stress is necessary for normal fetal development and signaling processes, excessive oxidative stress can be detrimental to fetal health (54). A balanced diet rich in antioxidants (such as vitamins C and E, and other phytochemicals) can help mitigate oxidative stress during pregnancy (55,56). It's important to note that while oxidative stress can have negative effects, it also plays essential roles in normal physiological processes.…”
Section: Oxidative Stress In Different Pregnancy-related Complicationsmentioning
confidence: 99%
“…[93] Other prospective studies have come to the opposite conclusion, suggesting that high vitamin A levels lead to GDM. [94]…”
Section: Vitaminmentioning
confidence: 99%
“…[93] Other prospective studies have come to the opposite conclusion, suggesting that high vitamin A levels lead to GDM. [94] 7. Trace element A study suggests that micronutrient supplementation during pregnancy is beneficial for patients with GDM.…”
Section: Vitaminmentioning
confidence: 99%